La belle indifference in conversion symptoms and hysteria: systematic review. - Stone, J; Smyth, R; Carson, A; Warlow, C; Sharpe, M (2006)
BACKGROUND: La belle indifférence refers to an apparent lack of concern shown by some patients towards their symptoms. It is often regarded as typical of conversion symptoms/hysteria. AIMS: To determine the frequency of la belle indifférence in studies of patients with conversion symptoms/hysteria and to determine whether it discriminates between conversion symptoms and symptoms attributable to organic disease. METHOD: A systematic review of all studies published since 1965 that have reported rates of la belle indifférence in patients with conversion symptoms and/or patients with organic disease. RESULTS: A total of 11 studies were eligible for inclusion. The median frequency of la belle indifférence was 21% (range 0-54%) in 356 patients with conversion symptoms, and 29% (range 0-60%) in 157 patients with organic disease. CONCLUSIONS: The available evidence does not support the use of la belle indifférence to discriminate between conversion symptoms and symptoms of organic disease. The quality of the published studies is poor, with a lack off operational definitions and masked ratings. La belle indifférence should be abandoned as a clinical sign until both its definition and its utility have been clarified.